PELATIHAN PEMANFAATAN GENERATIVE ARTIFICIAL INTELLIGENCE UNTUK LITERASI DIGITAL MAHASISWA STIDKI AL-AZIZ BATAM - Pastima Simanjuntak; Rika Harman; Yohanni Syahra; Herman Yuliansyah; Imam Riadi (PUAN INDONESIA, 2026)
The development of Generative Artificial Intelligence (AI) presents significant opportunities to support digital literacy and creativity in higher education. However, utilization of this technology among students still faces challenges, including limited understanding, technical skills, and ethical awareness. This community service activity was conducted on January 31, 2026, at STIDKI Al-Aziz Batam, involving 18 student participants from two study programs. The activity employed an educative-participatory approach comprising material presentations, interactive discussions, and hands-on practice sessions. Post-training evaluation was conducted using a Likert-scale questionnaire (scale 1-5) covering three dimensions: conceptual understanding, perceived benefits, and participant satisfaction. Results showed a mean score of 4.21 out of 5 (84.2%) for conceptual understanding of Generative AI, a mean perceived benefit score of 4.35 (87.0%), and an overall satisfaction score of 4.40 (88.0%). Furthermore, 88.9% of participants (16 of 18) met the minimum understanding threshold (score >= 4). These findings demonstrate that structured, practice based training significantly enhances students digital literacy competence and ethical awareness of AI use. The activity provides a tangible contribution to strengthening students digital capacities and is relevant for sustainable development.